2023
DOI: 10.3390/cancers15235652
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Antigen Receptor T-Cell Therapy for Glioblastoma

Kun Ma,
Ping Hu

Abstract: Glioblastoma (GBM), the most common primary brain tumor in adults, is characterized by low survival rates and a grim prognosis. Current treatment modalities, including extensive surgical resection, chemotherapy, and radiation therapy, often yield limited success due to the brain’s sensitivity, leading to significant side effects. Exciting advancements in immunotherapy have recently shown promise in treating various types of tumors, raising hopes for improved outcomes in brain tumor patients. One promising immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 107 publications
0
1
0
Order By: Relevance
“…For example, in a recent randomized phase III clinical trial focusing on programmed cell death pathway inhibition in GBM, the anti-PD-1 therapy failed to prolong overall survival in these patients [6]. Similarly, initial tumor regression noted in a clinical trial adoptive T cell transfer for GBM was subsequently followed by disease progression [7]. Despite these negative results, several studies showed that some patient subsets exhibit prolonged survival following this form of ICB [8,9].…”
mentioning
confidence: 99%
“…For example, in a recent randomized phase III clinical trial focusing on programmed cell death pathway inhibition in GBM, the anti-PD-1 therapy failed to prolong overall survival in these patients [6]. Similarly, initial tumor regression noted in a clinical trial adoptive T cell transfer for GBM was subsequently followed by disease progression [7]. Despite these negative results, several studies showed that some patient subsets exhibit prolonged survival following this form of ICB [8,9].…”
mentioning
confidence: 99%